Formation of protective surface films on carbon steel in mildly alkaline aqueous alkanolamine CO2 solutions. (February 2023) - Sadeek, Samara A.; Bedoya-Lora, Franky E.; Campbell, Kyra Sedransk; Kelsall, Geoff H.; Hankin, Anna
Abstract: Electrochemical impedance spectroscopy (EIS) and open circuit potential (OCP) measurements, complemented by solution speciation predictions and ex situ surface analyses, were used to investigate film formation on carbon steel in CO2 saturated methyldiethanolamine(aq) solutions at 80 °C, pH 7.9–8.6. Pure FeCO3 films, evidenced by OCPs of ca . −0.5 to −0.4 V (SHE), were formed under anoxic conditions and provided corrosion protection to the underlying substrate, increasing charge transfer resistances tenfold. O2 ingress caused a positive OCP shift to ca. > +0.35 V (SHE), resulting in formation of traces of iron oxide at the interface, which was less protective. Highlights: Pure FeCO3 films formed on carbon steel in anoxic CO2 – methyldiethanolamine – H2 O. FeCO3 films were porous and served as physical barriers rather than insulators. Iron oxide traces in FeCO3 films decreased film electrical resistivity. Open circuit potential is an indicator of otherwise imperceptible phases.